KARAKTERISTIK SENSORI BROWNIES CRISPY DENGAN PERBEDAAN PROPORSI TEPUNG UWI DAN PENAMBAHAN TEPUNG KELAPA - Shiva Fauziah; Ita Fathkur Romadhoni; Any Sutiadiningsih; Qorry’ Aina (Kampus Akademik Publiser, 2026)
This study aimed to determine the effect of varying proportions of wheat flour, uwi flour, and coconut flour on the sensory characteristics of crispy brownies. The experiment employed a completely randomized design with three treatments: Formula 1 (80%:10%:10%), Formula 2 (70%:20%:10%), and Formula 3 (60%:30%:10%). Sensory evaluation was conducted by 30 panelists using a 5-point hedonic scale to assess the attributes of color, aroma, texture, and taste. Data were analyzed using one-way ANOVA, followed by Duncan’s Multiple Range Test for treatments showing significant differences.The results showed that the variation in flour proportions did not produce significant differences in the scores for color (p>0,157), smell (p>0, 250), and texture (p>0,359). In contrast, a significant effect was observed on the taste attribute of the product (p < 0.05). Duncan’s test indicated that formulation F1 (80% wheat flour, 10% uwi flour, 10% coconut flour) yielded the best results based on panelist preference. These findings suggest that substituting wheat flour with uwi flour remains acceptable in terms of sensory characteristics to the panelists.